Analysis of Factors Affecting Entrepreneurial Interest of Vocational High School Students in Pekanbaru - Nurmaliza, Nurmaliza; Caska, Caska; Indrawati, Henny (Journal of Educational Sciences, 2018)
The highest unemployment rate (TPT) in Indonesia is fromgraduated of Vocational High School (SMK), which is 9.27%. Thisphenomenon cannot be separated from the low interest of entrepreneurship.SMK graduates are expected to be able to work directly and can openemployment area; the fact is far different from expectations. This study aimsto analyze the factors that affect student entrepreneurship interest in SMK.The population of this study was 1845 students of class XII SMK Negeri inPekanbaru City. The sampling method used in this research was SimpleRandom Sampling so that it obtained 329 students. The data collection usedquestionnaire with Likert scale that is suitable for exogenous variable(entrepreneurship interest), endogen variable (entrepreneurship educationand family environment), and intervening variable (personality). The dataanalysis technique employed the path analysis method. The results of theanalysis show that entrepreneurship education, and family environment havepositive and significant influence on entrepreneurship interest through thepersonality. This shows that interest in entrepreneurship can be enhanced ifthe quality of entrepreneurship education, family environment and studentpersonality are improved.